Kajian Studi Literatur Model Pembeajaran Discovery Learning untuk Meningkatkan Hasil Belajar Peserta Didik Pasca Pandemi Covid-19: Array - Rizki Kurniawan; Neviyarni; Herman Nirwana (Citra Dharma Cindekia, 2022)
This study aims to determine the increase in learning outcomes through the Discovery Learning learning model as a learning innovation that can be applied by educators after the Covid-19 pandemic. Through a literature review, the